NEW INSIGHTS FOR SOFT SKILLS DEVELOPMENT IN VIETNAMESE BUSINESS SCHOOLS: DEFINING ESSENTIAL SOFT SKILL PACKAGES FOR ADVANCED STUDENT LEARNING - Truong, Thi Thu Hang; Laura, Professor Ron (IJRDO - Journal of Business Management, 2017)
Within Vietnam's system of higher education, its schools of business play a vital role in supporting the country’s economic objectives. However, the crucial contribution of soft skills for maximal success within the business sector has to date not been adequately recognized by its business schools. This being so, the development of the business school curriculum in Vietnam has not been able to 'catch up', so to say, with the burgeoning need of students for a comprehensive soft skills program designed to meet the national and global business objectives of their potential employers(Duoc & Christopher, 2007; Ca, 2006). The burden of the present paper is first to reveal the results of our survey in Vietnam which make explicit the extent to which major Vietnamese industrial employers’ value the potential role which soft skill competencies can play in maximizing business success. Our second aim is to determine the extent to which Vietnamese employers are satisfied that graduates of Vietnamese business schools possess the soft skills competencies necessary to advance Vietnamese's ostensible goals of global business success. Based on our survey of employers' perceptions of both the soft skills needed by employees within Vietnam's primary industrial sectors, and whether graduating students are sufficiently equipped with these skills to work effectively enough to warrant their employment, our final task will be to determine what combination of soft skill packages employers discern as best serving to maximize the economic interests of Vietnam within the global marketplaceSemi-structured telephone interviews are conducted with 15 representative employers of Vietnam's reputedly largest business enterprises across Vietnam. The methodology of Manual Analysis is utilised to accommodate the small number of participantsThe findings of the study indicate that all 15 employers highly value the increasing importance of soft skills in business success. The respondents reveal the deficiency of soft skills among business graduates that impacts on the quality of their work. Our critical analysis of respondent data reveals that 19 essential soft skills are deemed by employers as integral to business workplace efficacy and should thus be integrated into the formal business curriculumWe are confident that our study represents the most comprehensive survey yet undertaken in Vietnam which accesses and analyses the opinions of representative employers from major companies across the country in regard to the growing importance of soft skills for overall business success. The research findings are especially pertinent to business training programs in Vietnam, and with minor adaptation, to other Asian countries